Evaluasi Kualitas Website Seleksi Masuk Mahasiswa Dengan Metode McCall - Gifthera Dwilestari; Nisa Dienwati Nuris (STMIK IKMI Cirebon, 2020)
The use of websites as a medium for disseminating information is a matter that is familiar in this era of digital technology. Telkom University which is a tertiary institution in Indonesia which often carries digital themes in its campus certainly does not want to be left behind in the use of websites as a medium for disseminating information and marketing for the community. This study aims to analyze the quality of the information system on the smb.telkomunivesity.ac.id New Student Selection website which is used as an information center for admission of new students as well as registration for Telkom University entrance selection with indicators of McCall's information system quality factors. Based on the results of the study, the smb.telkomuniversity website is concluded to be a good quality website and can provide benefits for its users